1991
DOI: 10.1002/jbmr.5650060310
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies comparison of renal cortical receptors for parathyroid hormone and parathyroid hormone-related protein

Abstract: Parathyroid hormone (PTH) and PTH-related proteins (PTHrP) interact with a common receptor in rat bone cells and in canine renal membranes with similar affinity, but PTHrP are substantially less potent than PTH in stimulating adenylate cyclase in canine renal membranes; in contrast, PTH and PTHrP are equipotent in stimulating adenylate cyclase in rat bone cells. This discrepancy has been largely viewed as reflecting differences in the relative efficiency of signal transduction of PTHrP between bone and kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The results showed distinct differences in both competitive binding studies and labelling affinities studies of PTHrP-1-34 in SaOS-2 and MCF7 cell lines. Interestingly, the Scatchard analysis of the binding data in both cell lines revealed the presence of 4,25,30,38 We focused after this on the differences in binding affinity of PTH and PTHrP in the two cell lines. It has been shown that positions 5 and 23 are critical in conferring specificity for the PTH1R.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed distinct differences in both competitive binding studies and labelling affinities studies of PTHrP-1-34 in SaOS-2 and MCF7 cell lines. Interestingly, the Scatchard analysis of the binding data in both cell lines revealed the presence of 4,25,30,38 We focused after this on the differences in binding affinity of PTH and PTHrP in the two cell lines. It has been shown that positions 5 and 23 are critical in conferring specificity for the PTH1R.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for these discrepant results may be the use of heterologous models, with membrane and cell preparations from different species, in earlier studies. This is supported by a recent interspecies comparison of PTH receptors on renal membranes: N-terminal fragments of PTHrP and bovine PTH were equipotent in stimulating adenylate cyclase in membranes from rat and human origin; however, PTHrP was 15-fold less potent in canine membranes (Orloff et al, 1991;Orloff et al, 1989 a). Both peptides had equal binding affinities in all three systems.…”
Section: Discussionmentioning
confidence: 88%
“…Human PTH [h-PTH (1-34), Asahi Kasei Pharma Co. Ltd., Tokyo, Japan] was dissolved in 0.1 M sodium acetate buffer (PH 7.2) containing 0.1% bovine serum albumin (Seto et al 1999). There is 4 amino-acid differences compared to rat PTH, but the activity or reaction of h-PTH to rat tissue are not different compared to those of rat PTH (Orloff JJ et al 1991). h-PTH (30 µg/ kg body weight) or its vehicle was administered subcutaneously 3 times a week for 2 or 4 weeks based on previous studies (Skripitz and Aspenberg 2001;Komatsubara et al 2005) (Fig.…”
Section: Experimental Designmentioning
confidence: 99%